Inhibits Follicular Development and Possibly Ovulation in Human Subjects as Shown by Ultrasound Follicle Tracking - H.Y. Goncim; E.S. Mador; J.O. Ogunranti (SAGE Publishing, 2010)
There is no evidence from literature to show the use of ultrasound follicle tracking to monitor ovulation in women on Ricinus communis contraception. In the present study 20 women desiring contraception, gave an informed consent to be scanned from day 9 to day 16 of one of their menstrual cycle to track for follicles. After taking one seed of Ricinus communis , the women were again scanned for the same duration. The result obtained showed normal follicular development before the administration of Ricinus communis and the abolition of follicular development in all the 20 volunteers after taking one seed of Ricinus communis ( Figs. 1a and 1b ). This result showed that one seed of Ricinus communis taken orally is capable of preventing ovulation in humans and hence its anticonceptive effect may be due in part to the prevention of ovulation.